Frontispiece: Nanoconfinement of the Low‐Temperature Dark Conglomerate: Structural Control from Focal Conics to Helical Nanofilaments. Issue 31 (4th June 2019) - Foley, Lee; Park, Wongi; Yang, Minyong; Carlson, Eric; Korblova, Eva; Yoon, Dong Ki; Walba, David M.
Abstract : Interesting things happen in smectic (lamellar) liquid‐crystal phases dominated by a tendency for saddle‐splay deformation of the layers. The two main ways this tendency is expressed is with the formation of either "dark conglomerate" or "helical nanofilament" phases. In this work, it is demonstrated for the first time that a mesogen preferring the dark conglomerate phase changes morphology to give the helical nanofilament phase when constrained physically in nanopores. For more details see the Communication by D. M. Walba, D. Y. Yoon et al. onpage 7438 ff.